Mechanical and Acoustic Emission Behavior of Mg-Li Based Alloys Compressed Before and After Pre-Deformation by Intensive Strain Methods - , Andrzej Pawełek (Archives of Current Research International, 2017)
The behavior of acoustic emission (AE) and its relationships with mechanisms of compression deformations of Mg-Li and Mg-Li-Al based alloys before and after the processing by intensive strain methods such as the ECAP (Equal Channel Angular Pressing) and the HPT (High Pressure Torsion) was examined. It was shown that the AE behaviour may be explained in terms of the collective, highly synchronized movements of the groups of many dislocations related to their acceleration as well as internal and surface annihilation. The intensity of AE in α single-phase of Mg-4Li based alloys is almost two orders of magnitude higher than that in pure Mg, and AE event rate reaches the maximum for Mg4Li alloy, what is imposed by the effect of Li addition, in leading to favoring of additional slip systems in prismatic and pyramidal planes. On the other hand the AE intensity in α+β two-phase of Mg-8Li based alloys rapidly decrease in comparison to that of single α phase. This is caused by very high diffusivity of lithium, which in consequence leading limitation the ability of dislocations to collective behavior. However, the AE intensity and activity in β single-phase of Mg-12Li based alloys is drastically low in comparison to α and α+β alloys. Two ranges of AE activity, observed in Mg12Li, is caused by high diffusivity of Li, which facilitating the processes of internal stress relaxation ensures generally high plasticity of β single-phase alloys. Moreover, the investigations of Mg9Li-Al based alloys have showed, that the AE increases together with the increase of Al concentration is the result of growing volume contribution of very efficient acoustically hexagonal α phase. The visible decrease of AE intensity and activity as well as increase in strength of alloys subjected to HPT and ECAP processing has been observed. Simultaneously the microstructure refinement of alloys after intensive strain processing was confirmed by electron (TEM) and optical microscopy technique. The possible explanation is discussed in terms of high increase of the density of immobile dislocations which strongly restrict ability to collective movement of source generate new dislocations. Also the hypothesis of possible contribution of slip along grain boundaries is discussed.